Embracing Fallibility in Quantitative Research: Thoughts and Remarks on Exploratory Factor Analysis and beyond - Gabriel, Marcelo Luiz Dias da Silva; Hair, Joseph F.; da Silva, Dirceu; Braga, Sérgio Silva [UNESP] (FapUNIFESP (SciELO), 2024)
Objective: errors are inevitable in the scholarly pursuit of truth, yet they are often seen as flaws rather than growth opportunities. This paper examines the tension between scholars’ inherent fallibility and rigorous academic research standards, particularly concerning quantitative methods such as exploratory factor analysis (EFA) and partial least squares structural equation modeling (PLS-SEM). The focus is on whether the academic community effectively balances the acceptance of errors as part of the learning process, with the relentless pursuit of truth and how this balance influences the advancement of knowledge within the context of evolving statistical tools needed to improve our understanding of complex global relationships. Provocations: if errors are fundamental to scientific progress, why does the academic community approach them with apprehension? This fear of mistakes may inhibit innovation, especially in fields such as quantitative methods research, where the stakes are high. Another question is whether the accessibility of user-friendly statistical software has led to a superficial understanding of complex methodologies, prioritizing convenience over depth. Conclusions: we advocate for a shift in how the academic community perceives errors toward viewing them as essential to the research process rather than as fatal flaws. Embracing a humble approach to pointing out mistakes and limitations, particularly with quantitative methods such as EFA and SEM, can create a more innovative and progressive research environment. We call for a cultural shift where constructive critiques are balanced with understanding our collective fallibility, with the ultimate goal of producing more impactful scholarship.
Abarcando a Falibilidade na Pesquisa Quantitativa: Reflexões e Observações sobre a Análise Fatorial Exploratória e Além
Keywords: academic rigor; exploratory factor analysis; quantitative methods; scientific fallibility; structural equation modeling (SEM)